Temporohyoid osteoarthropathy in two young horses. Issue 5 (11th March 2013) - Readford, PK; Lester, GD; Secombe, CJ
<x xml:space="preserve">Abstract</x> Two cases of temporohyoid osteoarthropathy (THO) in young Australian horses are described. The pathogenesis of THO is yet to be fully elucidated, but current theories include extension of infection from otitis media or interna to the temporohyoid joint or a primary but non‐infectious degenerative condition within the temporohyoid joint. The young age of the horses and the unilateral distribution suggested an infectious aetiology. Both horses partially responded to treatment with broad‐spectrum antimicrobial and anti‐inflammatory drugs with concurrent management of ulcerative keratitis. The management of violent head shaking in one horse included the administration of gabapentin, an anticonvulsant known to have antihyperalgesic effects and reduce neuropathic pain.